Synergies in Design and Health. The role of architects and urban health planners in tackling key contemporary public health challenges - Azzopardi-Muscat, Natasha; Brambilla, Andrea; Caracci, Francesca; Capolongo, Stefano (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Important public health improvements have been achieved over the past decades, but new challenges are emerging and progress cannot be taken for granted. Urban settlements host most of the global population, but they are also sources of several threats. The aim of the paper is to investigate the role of architects and planners in contributing to overcome these critical health challenges and propose strategic actions for collaboration with the public health workforce. Methods: Taking global trends and public health challenges as starting point, a scoping literature review has been conducted to illustrate the possible synergies that architecture and public health workforce should exploit to support population health improvement and tackle key public health challenges. Results: The built environment affects climate change and public health through the use of resources, site location, and green spaces. In architecture curricula, limited space is devoted to health and vice versa. There is an urgent need for recognition of the benefits of collaboration and cross-fertilisation between public health and planning workforce from local to global levels. Conclusion: Public health is evolving from a bio-medical to a socio-anthropological approach and architects/planners have fundamental roles; further collaboration, research and training are needed.